3D structural modeling of the Upper Bahariya Member in Abu Gharadig oil and gas field, North Western Desert, Egypt. (February 2019) - Abdelmaksoud, Ahmed; Ewida, Hatem F.; El-Habaak, Galal H.; Amin, Ahmed T.
Abstract: Abu Gharadig Field lies in the central portion of Abu Gharadig Basin of the northern part of the Western Desert of Egypt, about 256 km west of Cairo. Abu Gharadig Basin is considered as an E-W trending intracratonic basin. The Upper Bahariya Member is a clayey reservoir and represents one of the Late Cretaceous units. There is a need for identifying whether the petrophysical parameters of this member are related to the facies changes or the present structures. Therefore, detailed structural and petrophysical studies are required. The structural configuration of the Upper Bahariya Member is studied in the present case and the results of this study will form the basis for future petrophysical studies. The present study includes the delineation of the main structural elements of the studied member within the study area. The aim of the present study was achieved through building a 3D structural model using Petrel™ Schlumberger Modeling software by integrating twenty 2D seismic sections with four digital well logs and a check-shot survey. The interpretation of the resulted model shows that the Upper Bahariya Member was folded into doubly plunging anticline with a gentle plunge to SW and a relatively steep plunge to NE. The fold was dissected by a series of normal faults trending E-W to NW-SE. The anticline is asymmetric and exhibits sigmoidal shape. The axis has mainly a NE-SW orientation and exhibits changing of this orientation in the NE part to be ENE-WSW and in the SW part to be also ENE-WSW, relating to the effect of a rotational stress. Growth faulting and thinning of the studied member at the crest of the anticline suggest the syn-sedimentary tectonics. Thus, these structures are related to the Late Cretaceous right-lateral shear which led to the opening of the North Atlantic. Highlights: The Upper Bahariya Member is investigated structurally in Abu Gharadig field utilizing 3D structural modeling technique. The structural configuration is then matched with the global plate tectonic movements. This configuration is represented by a sigmoidal doubly plunging anticline with a series of normal faults (E-W to NW-SE). Some apparent right-lateral movements are noticed occurring along the intersecting normal faults. These structures are contemporaneous and related to the Late Cretaceous right-lateral shear.